Storytelling training to improve English literacy mastery for teachers of SD Negeri Sukoharjo, Semarang Regency - Mulyadi, Dodi; Santoso, Heri Dwi; Hardiyanti, Diana; Nugraheni, Yunita; Santosa, Budi Tri; Murdiana, Sesi (Community Empowerment, 2021)
A person's literacy level in a certain matter of how high his ability or skill in their spesific field. However, the problem faced by partners is the low level of English literacy in supporting learning. The priority of the program to be implemented is to improve (1) English literacy skills, (2) mastery of storytelling techniques, and (3) public speaking skills. Participatory methods, training, mentoring for partners, and evaluative were applied in the implementation of this activity. The output of this community service program is an increase in mastery of English literacy and speaking English in public, as well as knowledge of storytelling techniques.